2019
DOI: 10.4285/jkstn.2019.33.4.153
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of early acute antibody-mediated rejection in an human leukocyte antigen-incompatible and ABO-incompatible living-donor kidney transplant patient

Abstract: For successful human leukocyte antigen-incompatible (HLAi) or ABO-incompatible (ABOi) living-donor kidney transplantations (LDKTs), pretransplant desensitization is essential; however, early antibody-mediated rejection (ABMR) remains the most important complication after HLAi or ABOi transplantation. Here, we report a case of early acute ABMR in simultaneous HLAi and ABOi LDKT with preformed donor-specific antibody (DSA), despite desensitization. Dialysis-dependent, severe ABMR occurred with a rebound of pre-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The most common treatment options for CABMR patients are rituximab and IVIG, but their effectiveness is still controversial [ 8 - 10 ]. Some studies have shown that bortezomib is effective for antibody-mediated rejection [ 11 ]. For the treatment of CABMR, we used the same protocol, irrespective of the presence of dnDSA or C4d, unlike in previous studies, which treated the dnDSA (–) group less aggressively than the dnDSA (+) group [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common treatment options for CABMR patients are rituximab and IVIG, but their effectiveness is still controversial [ 8 - 10 ]. Some studies have shown that bortezomib is effective for antibody-mediated rejection [ 11 ]. For the treatment of CABMR, we used the same protocol, irrespective of the presence of dnDSA or C4d, unlike in previous studies, which treated the dnDSA (–) group less aggressively than the dnDSA (+) group [ 12 ].…”
Section: Discussionmentioning
confidence: 99%